Study of diglyme plasmas by mass spectrometry - Bigansolli, Antonio R.; Honda, Roberto Y. [UNESP]; Algatti, Mauricio A. [UNESP]; Mota, Rogério P. [UNESP]; Kayama, Milton E. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper deals with the study of the fragmentation process of diethylene glycol dimethyl ether (diglyme) molecule, i.e., (CH3OCH2CH2)2O; in low pressure RF excited plasma discharges. The study was carried out using mass spectrometry. The mass spectra were collected by a mass spectrometer operating in the mass range from 1 to 300 amu. Plasmas were generated within a stainless steel cylindrical chamber in a plane parallel plate electrodes plasma reactor configuration with 210 mm of internal diameter and 225 mm of length. The chamber is provided with eight lateral entrances, positioned at the mid plane between the electrodes, that may be used for setting optical, electrical and mass diagnostics and the low (mechanical pump) and high (turbo-molecular pump) vacuum systems. The vacuum inside the plasma chamber is monitored by Pirani™ (thermocouple) and Penning™ (inverse magnetrom) gauges. The turbo-molecular pump is coupled to the chamber through a gate valve and is used for cleanness purposes. The pressure is pumped down to 10-6 Torr, being the chamber purged with argon several times before each running of the experiment. The 13.56 MHz RF power was coupled to the chamber through an appropriate matching network. Mass spectrometry allowed one to follow the trends of several chemical species resulted from diglyme's molecule fragmentation for different values of pressure and RF power. The results showed that for a fixed pressure, the increase of the RF power coupled to the plasma chamber from 5 to 45 W produced a plasma environment much more reactive which reduces the population of the heavier species and increases the population of the lighter one. This fact can be attributed to the increase of the electronic temperature that makes predominant the occurrence of inelastic processes that promotes molecular fragmentation. From the point of view of the nonfouling characteristic of the plasma deposited diglyme films the ethylene-glycol structure, e.g., CH2CH2O (44 amu), is one the most important structure to be retained within the film composition if one wants to keep its functionality as is already shown in current literature. The experimental results suggest that if one wants to keep the monomer's functionality within the plasma deposited films resulting from such kind of discharges one must operate in low RF power conditions.
Keywords: Diglyme plasmas; Mass spectrometry; Molecular fragmentation; Optical spectroscopy